Documenting of care arrangements for children of mothers admitted to a psychiatric hospital: A South African case study - Dawood, Nisaar Ahmed (Department of Psychiatry and Mental Health, 2019)
Background: Enquiring about and documenting care arrangements for children of inpatient mothers with mental illness is paramount. Failure to do so could have a negative impact on the well-being of their children. Documenting care arrangements on admission signals good practice on the part of the admitting medical staff and ensures compliance with the requirements of the South African Children’s Act of 2004. This study explores the current practice at a large government run tertiary female inpatient psychiatric unit in Cape Town, regarding the enquiring and documenting practice within the first 24 hours of admission, of these care arrangements. Methods: The study is a cross sectional study using a mixed methods approach including: i) a case note audit of 100 consecutive patient folders examining the documentation of care arrangements within the first 24 hours of admission and ii) a structured self-administered questionnaire to professional staff working on the unit. Results: A total of 87 clinical folders were audited. Ninety nine percent of these folders had written down in them whether the women had children or not. Fifty eight percent of women had minor children and had 87 children between them. Fifteen percent of women had no care arrangements documented and 20% of women had unclear documentation of care arrangements. Fifteen completed staff questionnaires were returned. All staff agreed that it was important to ask the mothers about care arrangements. Conclusion: Significant more women that those identified on admission may have children who may have been in unsafe care arrangements at the time of their admission. There is room for improving the clarity of documenting of care arrangements and the enquiring into the specific care arrangements.